Determinants of Intrapartum Still Birth and Early Neonatal Death in a Periurban Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Stillbirth and early neonatal death is quite high in Bangladesh. The current study was undertaken to find out sociodemographic and pregnancy related risk factors that may exist with cases of stillbirth and death during first 7 days of life. This was a cross sectional study conducted at Institute of Child and mother health (ICMH) between February to June 2015. Mothers delivered still birth baby at ICMH and whose babies were admitted in neonatal ward immediately after birth for delay to cry were enrolled consecutively. Data was collected by interviewing mothers and reviewing hospital records using structured questionnaire. Follow up was done till 7 days. Data analysis was done with SPSS version 14 Among a total 116 mothers 83.6% came from rural areas, 48.2% belong to 20-25 years age group with mean age 23±5 year, 46.6% had primary education, 89.7% were primipara, and 62.9% had more than 4 antenatal visits in index pregnancy. Common pregnancy related problems were anaemia (85.3%), preeclampsia (41.4%), less fetal movement (31.9%), polyhydramnios (13.8%), oligohydramnios (12.9%), premature rupture membrane (58.6%), prolong labour 48.3%), malpresentation (8.6%) and urinary tract infection in 12.1%. About 69.8% delivered at hospital, 59% had normal vaginal delivery, instrumental delivery 17.2% and caesarean section in 24.1%. About 57.8% babies were born preterm. and 55.1% were low birth weight. During first 7 days of life 32% developed neonatal sepsis and 32.8% died. Cause of death as recorded was perinatal asphyxia (55.17%), hypoxic ischemic encephalopathy 17.2%, low birth weight with perinatal asphyxia in 35.6% and meconium aspiration syndrome 4.5%. Stillbirth and early neonatal deaths are obstetric catastrophe and has common overlapping risk factors. Risk specific interventions with special emphasis on improvement of quality of care throughout the phases of pregnancy, delivery and postpartum period is recommendedBangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 10-17